2011
DOI: 10.1007/s00392-011-0395-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of ST-segment elevation in lead aVR in the risk assessment of patients with acute pulmonary embolism

Abstract: ST-elevation in lead aVR is associated with a more severe course of APE, especially in patients with intermediate-risk. Therefore, aVR-ST-elevation might be useful in risk stratification of APE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 44 publications
0
35
2
Order By: Relevance
“…Twenty studies (4898 patients) reported data on in‐hospital mortality . Several ECG features were meta‐analyzed for this outcome (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty studies (4898 patients) reported data on in‐hospital mortality . Several ECG features were meta‐analyzed for this outcome (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Since the publication of the Daniel score, several other studies have investigated the use of ECG as a tool for PE prognostication. These studies expanded the use of ECG and included findings not included in the Daniel score, such as ST‐segment depression, ST‐segment elevation (STE), Qr in lead V 1 , right axis deviation (RAD), and P pulmonale, among others . A recent consensus article by the International Society of Electrocardiology, the International Society for Holter and Noninvasive Electrocardiology, and the Iberoamerican Forum of Arrhythmias in the Internet demonstrated the need for a formal and comprehensive evaluation of the evidence for the use of ECG to prognosticate PE …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the literature suggests that the distribution of STDV has consistent regularity and mechanisms [6][7][8][9][13][14][15][16]. STE in leads V1, III, aVR and STD in leads I and V4/ V5-V6 are frequently observed in APE [6,7,9].…”
Section: Discussionmentioning
confidence: 98%
“…ST-segment deviation (STDV) (elevation and/ /or depression) is another common ECG manifestation of APE [6][7][8]. STDV could occur in 3 specific ischemic patterns: (i) left ventricular (LV) subendocardial ischemic pattern; (ii) RV transmural ischemic pattern; and (iii) LV subendocardial plus RV transmural ischemic pattern [9].…”
Section: Introductionmentioning
confidence: 99%